FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBERDAYAAN DIGITAL MARKETING, DIGITAL DASAR –DASAR AKUNTANSI (KONSEP, PRINSIP, DAN TEORI) TERHADAP KINERJA UMKM DI PRAYA LOMBOK TENGAH - KARTINI, ENDANG; MIMBAR, LALU; IZRAWATI, IZRAWATI (Universitas Mahasaraswati K. Mataram, 2024)
The purpose of this study is to determine whether Digital Marketing, Digital Accounting Basics measured by E-commerce, E-commerce Applications, Benefits of E-Commerce in the business world, Benefits of E-Commerce for customers, E-Commerce Payment Processes, and Accounting Information System Components have a significant effect both simultaneously and partially on the performance of MSMEs in Praya Lombok. The population is all MSMEs as many as 3,988 samples taken 98 out of 3,988. The results of the study showed that the six independent variables each had a significant effect both partially and simultaneously on the performance of MSMEs, the coefficient value of the six positive variables means that there is a unidirectional relationship between the following five variables and MSME performance. The strength of the relationship between the independent and dependent variables indicated by the R value of 94.0% indicates that the correlation relationship is very strong. Variations in MSME performance are explained by variations in the six independent variables with a value of 87.5% indicated by adjusted R2, while the remaining 12.5% is explained by other causes outside the model. It was identified that in predicting the dependent variable, where seen from the Standard Error of Estimate (SEE) value of 0.142, it was concluded that the smaller the SEE value, the more accurate the regression model would be in predicting the dependent variable.